Triple Bottom-line Business Model. Case study on the organic food retailing - Ana Galeano Revert; José P. García-Sabater; Cristóbal Miralles Insa (WPOM : Working Papers on Operations Management)
The present work aims to analyse and identify a triple bottom-line business model of food retailing, in order to show a sustainable, replicable and non-scalable model in the agri-food sector, and to facilitate the development of a feasible market for small size producers-sellers. The methodology used for the business model identification analyses and relates elements and strategies, providing a design graphic for the model, as well as evaluating each triple sustainability dimension. All this following a protocol derived from the methodology of case study research. The case study shows a sustainable, replicable and non-scalable business model that emerges from a strategy defined by a responsible consumption group from a university. Using digital technology for the distribution and sale of products, and sharing capacity with a WISE, a business model is achieved that shortens the food products commercialization channel between producers and consumers, improving economic, social and environmental sustainability. The application of this methodology provides a tool that facilitates the replicability of sustainable business models in the agri-food business context, and allows identifying the level of their sustainability. The incorporation of this business model can contribute to the development of a triple bottom-line food market, whose purpose is to improve the survival of small size producers-sellers given the increasing centralization and globalization of the agri-food economy distribution.